A survey of the macroepiphytes of Mt. Balugo, Tacloban City - Amoylen, Agnetha Jane Mari; Cadavis, Maricel Pesao; Monge, Glenn Carrozo; Soledad, Donna Ann Santos
A survey of the macroepiphytes in Mt. Balugo, Tacloban City was conducted from January to February 2000. From the three different levels of the mountain, peak (80-120 m ASL), middle (60-80 m ASL), and bottom (20-60 m ASL), A total of 31 macroepiphytes were collected and classified except for 2 species remained unidentified. The middle part of the mountain (site B) had the highest number of species reaching a total of 26 and is the most diverse as indicated by the species richness index (10.85). It is followed by the bottom (site A) with a total of 13 species and the peak (site C) having 3 species only. Similarity index value between sites A and B is 0.41, and 0.21 between sites B and C suggesting an uneven distribution of the different epiphyte species in Mt. Balugo.